Strategies of coping with transgressor Polish validation of TIRM-18 Questionnaire - Marlena M. Kossakowska; Piotr Kwiatek (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The aim of this paper is to present the results of Polish validation of Transgression - Related Interpersonal Motivations questionnaire (TRIM-18) by McCullough, Root, and Cohen (2006) which measures the phenomena of forgiveness. The article contains a description of the procedure of Polish translation, the results of the test reliability, discriminant and confirmatory validity. The study was conducted among 530 participants aged between 18 and 84 (345 females and 185 males). Eleven questionnaires were used for assessing the validity of the measurement. This study confirms that the structure of Polish TRIM-18 is relevant to the English language version. Polish TRIM-18 is also a very reliable tool. It can be successfully used in Polish conditions.